Influence of Oregano (Origanum vulgare L.), Fennel (Foeniculum vulgare L.) and Hop cones (Humulus lupulus L.) on biogas and methane production - Mohamed, Shamseldin Daffallah Yousif; Justus Liebig University Giessen (My University, 2014)
A high demand for agricultural biomass production in Germany was attributed to the increasing number of biogas plants every year. The value of a crop as a substrate for biogas production via anaerobic digestion depends on its biomass yield capacity compared to the effort for cultivation and on its ability to produce biogas with high methane content.After the EEG 2012 amendment which determined the amount of maize that should be used in biogas production farmers searching for alternative substrates for biogas production. These alternatives can be cereal crops, vegetables, house hold wastes, grasses or farm residuals. Few farmers grow spices as marginal crops. The rests and residues of spices after harvesting can be used in the biogas plants. These spices contain secondary metabolites such as terpenes, flavenoids and other phenolic compounds. In the literature not enough studies can be found that focused on the effect of plant secondary metabolites on biogas and methane production through anaerobic digestion.The influence of plant secondary metabolites mainly terpenes in oregano leaves, fennel seeds and hop cones on biogas and methane production was investigated in this study.Two types of experiments were conducted. First two in vitro experiments were carried out using Methanosarcina barker as model for methanogens. It was cultivated in artificial bicarbonate buffered and sulfide reduced mineral media supplied with vitamins and trace minerals in serum bottles at mesophilic conditions. Oregano methanolic extract, carvacrol and thymol as main components of its essential oil were added at doses of 1.5 ml, 2.0 ml and 3.0 ml/50 ml of media. Carvacrol, thymol and their mixture were added at 0.1 and 0.3 ml/50 ml of media.Essential oil of oregano contains mainly carvacrol and thymol, p-cymene, limonene and α- and β-pinene in small quantities. The essential oil of fennel contains mainly trans-anethol, fenchone and estragol. The essential oil of hops contains mono and sesquiterpenes in addition to resins, flavonoids, glycosides and phenolic acids.It was found that the extracts of oregano at the concentration of 2.0 ml and 3.0 ml have clear negative effect on the activity of Methanocarcina barkeri to producemethane. Nevertheless the dose of 1.5 ml of oregano extract has no negative effect. All doses of carvacrol, thymol and their mixture showed negative effect on the methane. An increase in concentration of each of tested material was associated with a decrease in the methane production.In second type of experiments 46 parallel running 20 liter biogas digesters were fed with 15 kg cattle liquid manure 3-5% dry matter. The cattle liquid manure was brought from a second phase running biogas plant. Oregano was supplied at 62.5 g, 125 g, 250 g and 500 g/digester. Fennel seeds were added at 25 g, 50 g, 100 g, 200 g, and 400 g/digester. Hop cones were applied at 25 g, 50 g, 100 g, 200 g and 400 g/digester. In case of the inhibition test standard cellulose at 100 g/digester was mixed with the cattle liquid manure. Maize and standard cellulose were used as reference materials at concentration of 450 g and 100 g/digester respectively.Oregano in batch digesters at 250 g (16.7 g/kg manure) and 500 g (33.3 g/kg of manure) doses showed negative effect on the biogas and methane production and no methane was produced by the 500 g (33.3 g/kg manure) dose. Contrary the doses 62.5 g and 125 g showed positive effect. Fennel seeds at doses 200 g (13.3 g/kg manure) and 400 g (26.7 g/kg manure) have clear negative effect on biogas and methane production. Neither methane nor biogas was produced by all hop cones concentrations.The findings of the conducted study added valuable information about the inhibition of biogas by plant secondary metabolites found in oregano, fennel and hop cones.

Die hohe Nachfrage nach landwirtschaftlicher Biomasse in Deutschland wird der wachsenden Zahl an Nutzpflanzen für die Biogasproduktion pro Jahr zugeschrieben. Die Wertigkeit der Kultur als Substrat für die Biogasproduktion mittels anaerober Gärung ist abhängig vom Ertrag im Vergleich zum Arbeitsaufwand der Kultivierung und seiner Eignung Biogas mit hohem Methangehalt zu produzieren.Aufgrund der Änderung des EEG 2012 besteht ein verstärktes Interesse der Landwirte alternative Substrate für die Biogasproduktion zu finden, da der Einsatz von Mais limitiert wurde. Alternative Kulturen zur Herstellung von Biogas sind u.a. Getreide, Gemüse, Haushaltsabfälle, Gräser und Abfälle aus der Landwirtschaft. Die Überreste und Abfälle der landwirtschaftlichen Gewürzpflanzenproduktion können der Biogasproduktion zugeführt werden. Ebenfalls diese Gewürzpflanzen enthalten sogenannte sekundäre Pflanzeninhaltsstoffe wie Terpene, Flavonoide und andere phenolische Komponenten. In der Literatur existieren nicht ausreichend Studien, die den Effekt sekundärer Pflanzeninhaltstoffe auf die Biogas- und Methanproduktion mittels anaerober Gärung untersuchen.Der Einfluss sekundärer Pflanzeninhaltstoffe, vorwiegend Terpene, aus Oregano-Blättern, Fenchelsamen und Hopfenzapfen auf die Biogas- und Methanproduktion wurden in dieser Arbeit untersucht.Zwei verschiedene Experimente wurden durchgeführt worden. Als erstes wurden zwei in vitro Versuche mit Methanosarcina barkeri als Modell für Methanogene durchgeführt. Die Kultivierung wurde in künstlichen bikarbonatgepufferten und sulfitreduzierten Mineralmedium, angereichert mit Vitaminen und SL 10 Spurenelementen, in Serumflaschen unter mesophilen Bedingungen durchgeführt. Das methanolische Oreganoextrakt enthält als Hauptkomponenten des ätherischen Öls Thymol und Carvacrol. Die Extrakte wurden in folgenden Konzentrationen dem Medium zugeführt; 1,5 ml, 2,0 ml und 3,0 ml zu je 50 ml medium. Carvacrol, Thymol und deren Gemisch wurden bei 0,1 und 0,3 ml pro 50 ml Medium zugegeben.Das ätherische Öl des Oregano enthält überwiegend Carvacrol und Thymol, sowie p- Cymen, Limonen und α- andβ-Pinen in Spuren. Das ätherische Öl des Fenchels enthält vorwiegend trans-Anethol, Fenchon und Estragol. Im ätherischen Öl desHopfens sind Mono- und Sesquiterpene, Harz, Flavonoide, Glykoside und Phenolsäuren enthalten.Die Untersuchung von 2,0 ml und 3.0 ml Extrakt aus Oregano weist einen deutlich negativen Effekt auf die Methanproduktion von Methanocarcina barkeri auf. Die Dosis von 1,5 ml Oreganoextrakt weist keinen negativen Effekt auf die Methanproduktion auf. Carvacrol, Thymol und ihr Gemisch zeigen bei allen Konzentrationen einen negativen Effekt auf die Methanproduktion. Die Anhebung der Konzentrationen jedes getesteten Materials ist mit einer Abnahme der Methanproduktion assoziiert.In einem zweiten Biogasexperiment sind 46 Batchbehälter (20Liter)mit 15 kg flüssigerRingergülle gefüllt worden. Die Rindergüllestammt aus einer zwei-phasigen Biogasanlage.Oregano ist in Dosen von 62,5 g, 125 g. 250 g und 500 g pro Fermenter hinzugefügt worden. Fenchelsamen sind mit je 25 g, 50 g, 100 g, 200 g und 400 g pro Fermenter zugegeben worden. Hopfenzapfen sind mit 25 g, 50 g, 100 g, 200 g und 400 g pro Fermenter zugegeben worden. Für den Fall einer Enzymhemmung ist standardmäßig 100 g Zellulose beigegeben worden. Mais und Zellulose sind als Referenzsubstanzen (450 g und 100 g pro Fermenter) genutzt worden.Die Verwendung von 250 g (16.7 g/kg Rindergülle) und 500g (33.3 g/kg of Rindergülle) Oregano weist einen negativen Effekt auf die Biogas- und Methanproduktion auf. Bei 500 g wird kein Methan mehr produziert. Im Gegensatz dazu führen Konzentrationen von 62,5 g und 125 g zu einem verstärkenden Effekt auf die Biogas- und Methanproduktion. Die Zugabe von 200 g (13.3 g/kg Rindergülle) und 400 g (26.7 g/kg Rindergülle) Fenchelsamen resultiert in einem deutlich negativen Effekt auf die Biogas- und Methanproduktion. Weder Methan noch Biogas konnte von den Hopfenzapfen produziert werden.Die Ergebnisse dieser Arbeit geben wertvolle Informationen zur Inhibierung der Biogasproduktion durch sekundäre Pflanzeninhaltsstoffe, wie sie in Oregano, Fenchel und Hopfen ermittelt werden.
Einfluss auf Oregano (Origanum vulgare L.), Fencel (Foeniculum vulgare L.) und Hopfen (Humulus lupulus L.) auf Biogas und Methanproduktion
Keywords: Biogas; Methan; Hopfen; Oregano; Fenchel; Oregano; Fennel; Hop; biogas; methane; ddc:630